A comparison of the LS CE-Chirp and click evoked auditory brainstem response stimuli for neuro-diagnostic assessment in order to determine the preferable stimulus - Biagio de Jager, Leigh (University of Pretoria, 2024)
Dissertation (MA (Audiology))--University of Pretoria, 2019.